2004
DOI: 10.1097/00005537-200408000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Surgical Management of Nasopalatine Duct Cysts

Abstract: Nasopalatine duct cyst occurs in approximately 1% of the population. Presentation may be asymptomatic or include swelling, pain, and drainage from the hard palate. A well-circumscribed, round, ovoid, or heart-shaped radiolucency is seen on computed tomography. Pathological findings reveal squamous or respiratory cell types, or a combination of these, infiltrated by inflammatory cells. Enucleation is the preferred treatment with low recurrence rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 17 publications
1
50
0
16
Order By: Relevance
“…In addition, Choi et al [12] reported the occurrence of eight cases of nasolabial cyst over a period of only 1 year and suggested that these cysts may be more common than previously thought. A predominance of nasolabial cysts among females has been reported [5,32], with a female/male ratio ranging from 2.2:1 to 6.1:1 [11][12][13]. Most cases are diagnosed in the fourth and fifth decades of life [3,12,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Choi et al [12] reported the occurrence of eight cases of nasolabial cyst over a period of only 1 year and suggested that these cysts may be more common than previously thought. A predominance of nasolabial cysts among females has been reported [5,32], with a female/male ratio ranging from 2.2:1 to 6.1:1 [11][12][13]. Most cases are diagnosed in the fourth and fifth decades of life [3,12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of studies on nOCs in the literature [3,[10][11][12][13][14], information regarding the demographic profile of these lesions in different populations is scarce [1,2]. Thus, the aim of the present study was to determine the distribution of nOCs in the oral and maxillofacial region diagnosed histologically over a period of 40 years in a Brazilian population according to age, gender and site affected, and to compare the results with literature data.…”
Section: Introductionmentioning
confidence: 99%
“…13 The physical examination demonstrates swelling in the hard palate, and CT shows a well-defined rounded or oval lesion in the mid-maxillary area. 13 CT or MRI reveal the soft-tissue origin of nasolabial cysts, which avoids unnecessary dental surgery or needle aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…13 The physical examination demonstrates swelling in the hard palate, and CT shows a well-defined rounded or oval lesion in the mid-maxillary area. 13 CT or MRI reveal the soft-tissue origin of nasolabial cysts, which avoids unnecessary dental surgery or needle aspiration. 7 CT usually shows a homogeneous, non-contrast enhancing cystic lesion 11,14 anterior to the pirifom opening; remodeling of the underlying maxillary bone may be seen in larger cysts.…”
Section: Discussionmentioning
confidence: 99%
“…9 Çok geniş NPKK'lere cerrahi öncesi marsüpyalizasyon yapılması önerilmektedir. 8,17 Kanal içerisindeki nazopalatin damar sinir paketinin yüksek vaskülarizas-yon göstermesinin göz önünde bulundurulması, cerrahi işlem sırasında kanama kontrolü açısından önemlidir. Lezyonların tamamen çıkartılmaları sonrası nüks etmeleri nadirdir.…”
Section: Introductionunclassified